PEMBENTUKAN NILAI-NILAI AKHLAQUL KARIMAH MELALUI POLA INTERAKSI GURU DENGAN ORANG TUA - Fatimah Uswatun Khazanah; Jumari (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2021)
As the habituation of morality carried out at Madrasah Tsanawiyah Negeri 1 Jombang. This madrasa makes efforts to form moral values for students andstudents through a pattern of interaction between teachers and parents themselves in order to provide future provisions for them. Not only getting used to moral values, but also training students to be active in all activities. This can be seen when at 06.00 in the morning all students have to gather at the Madrasah after that at 06.20 the students will be led to the mosque to perform the dhuha prayer in congregation, after praying in congregation the students will return to doing as usual. This article uses a qualitative field research approach based on observations, interviews, and documentation with qualitative descriptive analysis as well as checking the validity of the data and triangulation. The results of this study are in the form of technical and mechanism which include understanding, intent and purpose of efforts to form moral values in students, activities that encourage moral values in a student, and patterns of cooperative interaction between teachers and parents to form moral values in the students themselves. Factors that influence the effort to form the moral values of students are human resources and the development of the times (the science of technology)